2020
DOI: 10.1038/s41437-020-0326-8
|View full text |Cite
|
Sign up to set email alerts
|

Applying genomic resources to accelerate wheat biofortification

Abstract: Wheat has low levels of the micronutrients iron and zinc in the grain, which contributes to 2 billion people suffering from micronutrient deficiency globally. While wheat flour is commonly fortified during processing, an attractive and more sustainable solution is biofortification, which could improve micronutrient content in the human diet, without the sustainability issues and costs associated with conventional fortification. Although many studies have used quantitative trait loci mapping and genome-wide ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 77 publications
0
30
0
1
Order By: Relevance
“…Velu et al [4] concluded that dietary supplements and agronomic practices involving the use of Feand Zn-containing fertilizers can help address the nutrient deficiency problem. However, a sustainable and cost-effective approach to increasing essential mineral concentration is through genetic biofortification, which requires identification of cultivars with useful genetic variability for grain minerals and understanding of the physiological and genetic architecture of these minerals in wheat [6].…”
Section: Introductionmentioning
confidence: 99%
“…Velu et al [4] concluded that dietary supplements and agronomic practices involving the use of Feand Zn-containing fertilizers can help address the nutrient deficiency problem. However, a sustainable and cost-effective approach to increasing essential mineral concentration is through genetic biofortification, which requires identification of cultivars with useful genetic variability for grain minerals and understanding of the physiological and genetic architecture of these minerals in wheat [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, being polyploid and having a large genome are compelling factors in wheat breeding. Thus, without a genome sequence, it has been difficult to design molecular markers and map loci that regulate the desired trait (Ali and Borrill 2020). A wheat landrace Chinese Spring genome sequence (Ref-Seqv1.0) representing 94% of the whole wheat genome was published in 2018, and the high contiguity of this genome assembly was reported to be effective in genetic mapping of loci involved in Fe and Zn accumulation (Appels et al 2018).…”
Section: Genomic Approachesmentioning
confidence: 99%
“…One major way to overcome the constraints due to climate change and papaya diseases is by breeding for new and improved papaya that has been enhanced with desired traits, such as resistance to disease, resistance to abiotic stress, delayed ripening, and sweetness. Recent trends in crop improvements have shown the integration of omics approaches (i.e., genomics, transcriptomics, proteomics, and metabolomics) and bioinformatics in breeding programmes [16][17][18][19]. The use of omics and bioinformatic approaches in crop breeding helps to obtain a holistic understanding of the genetic and genomic bases of the crop, as well as to understand the molecular interaction among genes, proteins, and metabolites, especially regarding complex traits.…”
Section: Introductionmentioning
confidence: 99%